2018
DOI: 10.3390/environments5010016
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Activity of the Iron-Containing Natural Composites in the Reaction of Oxidative Destruction of Oxalic Acid and Phenol

Abstract: This paper presents the results of a study of the photocatalytic activity of iron-containing composites based on natural peat and zeolite under external influences: Ultraviolet irradiation (UVI) and UVI + H 2 O 2 . It is shown that the optimal method for the photocatalytic destruction of pollutants (oxalic acid and phenol) with composites is to introduce hydrogen peroxide in the system. The composites studied are sources of iron ions in the Ruff-Fenton system; they provide the generation of •OH radicals, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…The "−" sign corresponds to a unidirectional change of D 1 and D 2 relatively D 0 , i.e., D 1 and D 2 > D 0 or D 1 < D 0 , D 2 < D 0 . The "±" sign corresponds to a multidirectional change of D 1 and D 2 relatively D 0 , i.e., D 1 < D 0 and D 2 > D 0 or D 1 > D 0 , D 2 < D 0 [26].…”
Section: Modification Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The "−" sign corresponds to a unidirectional change of D 1 and D 2 relatively D 0 , i.e., D 1 and D 2 > D 0 or D 1 < D 0 , D 2 < D 0 . The "±" sign corresponds to a multidirectional change of D 1 and D 2 relatively D 0 , i.e., D 1 < D 0 and D 2 > D 0 or D 1 > D 0 , D 2 < D 0 [26].…”
Section: Modification Methodsmentioning
confidence: 99%
“…In our previous work [21][22][23][24][25][26], we showed that the composites, obtained by modifying natural sorbents (zeolites and peat) by metal ions (M n+ ), exhibited high catalytic activity in conditions of UVI and the Ruff-Fenton system during degradation of organic pollutants in aqueous media.…”
Section: Introductionmentioning
confidence: 99%
“…Natural zeolites, or, more precisely, natural zeolite-bearing rocks such as zeolitic-rich tuffs, have been widely utilized in various fields pertaining agro-environmental topics [1][2][3][4][5][6][7][8], from the increasing of soil fertility lato sensu to the cleaning of contaminated sites [9][10][11][12][13][14][15][16]. A novel, interdisciplinary field of zeolites application deals with pedotechnologies [17][18][19][20][21][22][23][24][25][26], i.e., a specific branch of soil science devoted to improve or even ex novo restoring the whole soil functions [27,28].…”
Section: Introductionmentioning
confidence: 99%